Diagnostic value of Transvaginal Ultrasonography in abnormal uterine bleeding compared with Dilatation and Curettage in perimenopausal women - Habibeh Salehi Aali; Roghayeh Darghi; Farahvash Parvin Darabad; Pouran Akhavan Akbari; Solmaz Fathi (Mashhad University of Medical Sciences, 2017)
Introduction: Abnormal uterine bleeding (AUB) is a common gynecological problem in peri-menopausal women which needs proper evaluation. Diagnostic procedures for detection of uterine pathological lesions include endometrial biopsy, Transvaginal ultrasonography, diagnostic hysteroscopy and dilation and curettage (D&C). Regarding to the importance of uterine bleeding for proper treatment, this study was performed with aim to compare diagnostic value of Transvaginal ultrasonography with dilation and curettage (D&C).to determine the causes of abnormal uterine bleeding in perimenopausal women. Methods: This descriptive-analytic study was performed on 94 women with abnormal uterine bleeding referred to Ardabil Alavi hospital from 2013 to 2015. After completing the demographic questionnaire, pelvic examination and Pap smear, transvaginal sonography (TVS) and dilatation and curettage (D&C) were performed for all patients. Data analysis was done using SPSS software (version18) and Cochrane test, determination of sensitivity and specificity and positive predictive value (PPV) and negative predictive value (NPV). P <0.05 was considered significant. Results: Myoma was the most common pathological lesion in both TVS and D&C methods (65.9% and 60.6 %, respectively). Sensitivity of TVS for detecting of myoma and endometrial polyp were 59.5% and %51.2, respectively and the specificity was 83.2% and 72/5%, respectively. PPV and NPV of TVS for diagnosis of myoma were 42.2%, 57.4% and for diagnosis of endometrial polyp were 61.4% and 39.9%, respectively. Sensitivity and specificity of TVS in the diagnosis of normal and abnormal bleeding) was 59.5% and 65.4%, respectively. PPV and NPV was 12.4% and 84.58%, respectively. The sensitivity and specificity of TVS in the correct diagnosis of patients with abnormal bleeding was 87.5% and 94.5%, respectively. PPV and NPV of TVS was 26.5% and 37.86%, respectively. Conclusion: Due to the high sensitivity and specificity of transvaginal sonography in the correct diagnosis of abnormal bleeding and non-invasiveness and low cost of this method, it is suggested as the first step in the evaluation of patients with abnormal bleeding.